Humanized Mice Engrafted With Human HSC Only or HSC and Thymus Support Comparable HIV-1 Replication, Immunopathology, and Responses to ART and Immune Therapy - Cheng, Liang; Ma, Jianping; Li, Guangming; Su, Lishan (Frontiers in Immunology, 2018)
Immunodeficient mice reconstituted with human immune tissues and cells (humanized mice) are relevant and robust models for the study of HIV-1 infection, immunopathogenesis, and therapy. In this study, we performed a comprehensive comparison of human immune reconstitution and HIV-1 infection, immunopathogenesis and therapy between immunodeficient NOD/Rag2−/−/γc−/− (NRG) mice transplanted with human HSCs (NRG-hu HSC) and mice transplanted with HSCs and thymus fragments (NRG-hu Thy/HSC) from the same donors. We found that similar human lymphoid and myeloid lineages were reconstituted in NRG-hu HSC and NRG-hu Thy/HSC mice, with human T cells more predominantly reconstituted in NRG-hu Thy/HSC mice, while NRG-hu HSC mice supported more human B cells and myeloid cells reconstitution. HIV-1 replicated similarly and induced similar T cell depletion, immune activation, and dysfunction in NRG-hu HSC and NRG-hu Thy/HSC mice. Moreover, combined antiretroviral therapy (cART) inhibited HIV-1 replication efficiently with similar persistent HIV-1 reservoirs in both models. Finally, we found that blocking type-I interferon signaling under cART treatment transiently activated HIV-1 reservoirs, enhanced T cell recovery and reduced HIV-1 reservoirs in both HIV-1 infected NRG-hu HSC and NRG-hu Thy/HSC mice. In summary, we report that NRG-hu Thy/HSC and NRG-hu HSC mice support similar HIV-1 infection and similar HIV-1 immunopathology; and HIV-1 replication responds similarly to cART and IFNAR blockade therapies. The NRG-hu HSC mouse model reconstituted with human HSC only is sufficient for the study of HIV-1 infection, pathogenesis, and therapy.